Potensi Ruh, Nafs, Akal, Qolb, dan Fitrah sebagai Bekal Manusia dalam Menjalankan Peran sebagai Abdullah - Santoso, Joko; Rohimah, Siti (TSAQOFAH, 2026)
Human beings are created by Allah SWT with the primary purpose of worshipping and devoting themselves to Him as ‘Abdullah, endowed with fundamental potentials in the form of ruh, nafs, akal, qolb, and fitrah that are intrinsically integrated. This article aims to conceptually examine the roles and functions of these five potentials in shaping human beings who are able to actualize complete servitude to Allah. The study employs a descriptive qualitative approach through a literature review based on the Al-Qur’an, Hadith, and the thought of classical and contemporary Muslim scholars and intellectuals. The findings show that ruh functions as the source of spiritual life, nafs as the dynamic of the soul that must be controlled, akal as the instrument of reasoning within the framework of revelation, qolb as the center of moral and spiritual consciousness, and fitrah as an innate purity that directs human beings toward tauhid. The balanced integration and management of these five potentials constitute the key for humans to actualize themselves as true ‘Abdullah. These findings underscore the importance of holistic Islamic education in developing the entirety of human potential in order to achieve balance among physical, intellectual, emotional, and spiritual dimensions.